Bike stunt gone wrong – Fatal Impalement by Liquor Bottle, landing into the death (Indian Internet Journal of Forensic Medicine and Toxicology, 2023)
Sharp force injuries are the leading cause of death worldwide. Accidental deaths  due to sharp force wounds are extremely rare compared to homicide and suicide  cases. Therefore, their exact incidence or prevalence is not accurately known. This  paper presents an accidental death due to massive blood loss resulting from the  sharp cutting of the left femoral artery by glass fragments that impaled the left  groin region of a young male. He was allegedly performing a bike stunt under  the influence of alcohol. The body was found in a pool of blood, surrounded by  multiple glass fragments from a broken alcohol bottle that was lying shattered  next to the body. The autopsy revealed a near-total transection of the left femoral  artery and significant glass injuries to the skin. Evidence of self-mutilation and  scarification in multiple body regions highlighted risky behavior. To determine  the circumstances of death in cases of accidental glass injuries, a thorough medico legal investigation, including details of the death scene, post-mortem examination,  and chemical analysis of viscera for any intoxicants or stupefying agents, is always  necessary.
Keywords: Injuries; Margins; Safety; Impalement; Examination